Micelle Formation and Surface Adsorption of Sodium 4-Octyl Benzene Sulfonate (S4OBS) in Water Solvent - Muhammad Rusdi (Jurnal Matematika & Sains, 2009)
The surface tension was measured against the concentration of S4OBS at temperatures of 300.2, 308.2, and 318.2 K, from which the critical micelle concentration (CMC) was determined. The CMC decreased with increasing temperatures. The thermodynamic parameters (DGo, DHo and DSo) of the micelle formation were calculated from the temperature dependence of CMC and the micellization was found to be entropy-driven. The surface excess concentration (G) was also determined from the change in the surface tension with the concentration from which the molecular surface area (A) below the CMC was evaluated. The molecular surface area suggests that thermal agitation at higher temperature more dominant than at lower temperature. The positive entropy change (DSo) for the surface adsorption decreased and stayed almost constant with increasing concentration of S4OBS.